'Did you read my mind on that too?': Empathy and Masculinity in Japanese Film and Television. Issue 2 (December 2015) - Barber, Christie
Abstract : Empathy involves both affective and cognitive processes: experiencing the other person's emotion and the attribution of theory of mind, which refers to the ability to ascribe an independent mental life to oneself and others. Strategies of engagement used in film and television can invite viewers to apply empathic processes to fictional characters. Such empathic engagement provides stimulation and enjoyment, and prompts viewers to anticipate and integrate information about characters and the narrative. This article examines the ways in which empathic engagement is developed in various Japanese film or television texts. These texts encourage viewers to empathise with young male protagonists who embody forms of marginalised or subordinated masculinity. As a result, the texts not only create a space for viewers to empathise in thought-provoking ways with fictional others, but also invite readers to interpret the protagonists as models of behaviour for dealing with common problems faced by young people, such as the pressure of social expectations and rejection by peers. Further, the films present a challenge to established gender norms through positive portrayals of marginalised or subordinated male protagonists.